Prediction of potentially suitable areas for the introduction of Magnolia wufengensis under climate change. (August 2021) - Shi, Xiaodeng; Yin, Qun; Sang, Ziyang; Zhu, Zhonglong; Jia, Zhongkui; Ma, Luyi
Highlights: We firstly predicted the potential suitable areas of Magnolia wufengensi in the world. The optimized Maxent model with climate, topography and soil variables was used. The low temperature variables were the most important environmental variables. The suitable area of M. wufengensis was mainly located in eastern and central Asia. The suitable areas will be greatly reduced and shifted northeast in the future. Abstract: Magnolia wufengensis, a new species of the subgenus Magnolia, has extremely high ornamental and scientific value due to its rich morphological diversity. The wild population of M. wufengensis has a narrow habitat and a sparse population, and is in a critically endangered state. Currently, the potential suitable areas for the introduction of M. wufengensis and the limiting factors affecting its distribution and the response to global warming are unclear. Hence, an optimized MaxEnt model in the ENMeval package based on 49  M. wufengensis occurrence records and 16 environmental variables were used to simulate the potential suitable areas for M. wufengensis under current and future (2041–2080) climate change scenarios, including four representative concentration pathways (RCP2.6, RCP4.5, RCP6.0 and RCP8.5), to provide a scientific basis for the precise introduction, cultivation and expansion of suitable areas of M. wufengensis . The MaxEnt model was highly accurate, with an average training area under the curve (AUC) value of 0.9895 ± 0.0011 after 10 repetitions. The results indicated that the mean temperature of the coldest quarter (-6.75–14.31 °C), mean diurnal range (≤14.29 °C), min temperature of the coldest month (-13.73–10.77 °C), mean temperature of the warmest quarter (≥12.93 °C), precipitation of the wettest month (40.99–715.42 mm) and annual mean temperature (4.47–24.56 °C) were the most important environmental variables (threshold) limiting the distribution of suitable areas for M. wufengensis . In the current climate, areas of 146.15 × 10 4 km 2, 119.88 × 10 4 km 2 and 224.87 × 10 4 km 2 were projected as potential areas with high, medium, and low suitability for M. wufengensis, respectively. These areas were mainly located in eastern and central Asia, the Mediterranean coast of southern Europe, and western America. Under future climate change, the potential suitable areas for M. wufengensis in the world will be greatly reduced, and the degree of fragmentation will increase. In addition, the reduction in suitable areas of different classes will be approximately 4.75%-39.14%, the suitable areas in western America and southern Europe will disappear, and the centroids of suitable areas for M. wufengensis will tends shift northeast.